Nonlinear fiscal multipliers in Saudi Arabia - Raja Almarzoqi; Sarra Ben Slimane; Saud Altamimi (Economies, 2023)
This paper presents an estimation of the fiscal multipliers for Saudi Arabia, conducted by applying the local projection (LP) method. It also presents an exploration of the non-linear features of fiscal multipliers. The findings showed that (i) consistent with earlier studies, fiscal multipliers are generally moderate; (ii) the investment spending multiplier is larger in magnitude than the current spending multiplier; (iii) the non-oil revenue multiplier is negative; (iv) the output response to fiscal shocks is larger during expansions; and (v) fiscal multipliers are stronger during a contractionary fiscal policy phase.
Keywords: 330; government spending; local projection method; non-linear fiscal multipliers; non-oil revenue; Saudi Arabia